Factors affecting time of spontaneous delivery of dichorionic diamniotic twin pregnancy - Hefila, Nermeen Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The incidence of twin pregnancy has markedly increased recently due to ART and advanced maternal age. The mother may also experience higher obstetrical morbidity and mortality rates. Aim of the work was to investigate factors affecting the time of spontaneous delivery in dichorionic diamniotic twin pregnancy to improve perinatal outcomes. Methods: The study was a cross-sectional study had been conducted at Elshatby university maternity hospital between October 2019 to May 2020 on 150 cases of dichorionc diamniotic twins pregnancy admitted for spontaneous delivery. History was taken from all women including general, abdominal and vaginal examination to assess pelvic capacity, first twin presentation, amniotic membrane state and cervical os measurements including cervical dilatation, effacement, station and orientation. Results: In our study ART twin pregnancies are higher than spontaneous pregnancy regarding the complications. In group A, we found that the uterine contractions are more frequent (6.5 times/30 min) and in B was (6.3 times/30 min) while in group C (2.8 times/30 min) (P<0.001). The cervical dilatation in group A on admission was statistically significant compared with the group B and C (p<0.001). PROMs (p=0.042) and incompetent internal os of cervix (IIOC, p<0.001) found to be the most important factor affecting the time of twin delivery specially before 36 weeks. Conclusions: The frequency and potency of uterine contractions, the cervical internal os dilatation and the state of amniotic membrane are the most important factors affecting the time of delivery in twin pregnancy.